Penerapan Manajemen Konflik untuk Meminimalisir Permasalahan Komunikasi dan Meningkatkan Solidaritas Anggota IPPMST Malang - Burhan, Rofiatul Jannah; Maulidina, Syifa; Hasanati, Nida; Djudiyah (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The Central Sulawesi Student and Youth Association (IPPMST) Malang is a regional organization that serves as a forum for togetherness, cultural preservation, and self-development for students living away from home. IPPMST Malang faces internal problems such as weak organizational communication, lack of member involvement in decision-making, and conflicts between members. This empowerment project aims to minimize communication problems and increase member solidarity through the application of conflict management. The methods used include literature studies, in-depth interviews, focus group discussions (FGD), and interventions in the form of conflict management training based on Rahim's theory. The intervention was carried out through psychoeducation, interactive discussions, and role-playing, with evaluation using pre-tests and post-tests based on the Rahim Organizational Conflict Inventory II (ROCI-II) instrument. The results showed a significant difference between the pre-test and post-test scores (p < 0.05). These findings indicate that conflict management training is effective in improving understanding, communication skills, and strengthening solidarity and cooperation among organization members.